PROSPEK USAHA PENGGEMUKAN SAPI BRAHMA DI KABUPATEN OKU TIMUR - Parmaji (Jurnal Bakti Agribisnis, 2017)
The purpose of this study is to: (1) To know the cost of production, acceptance and income of brahman cattle fattening in Eastern OKU, (2) To know the added value of brahman cattle fattening in East OKU, (3) Feasibility of brahman cattle fattening business in East OKU Regency. The research was conducted in OKU Timur Regency, with purposive determination of the research location with the consideration that there are still a few businessmen of cattle fattening who choose to fatten brahman cow, whereas the brahman cattle fattening in OKU Timur Regency has good prospect. This is because demand brahman cows from year to year continues to increase, in addition to the brushed cattle brewing process is quite easy and in a relatively long time has gained profits. This research has been conducted in March 2015 until May 2015 on the brahman cattle fattening that already existed in East OKU Regency. This study found that the average cost of production for brahman cattle fattening business is Rp. 79.438.224, - / PP, with a flat fee of Rp. 3,588,335, - / PP, and variable cost of Rp. 75.849.889, - / PP. Receipt is Rp. 123.333.333, - / PP then obtained revenue of Rp. 43.895.109, - / PP (Rp 7,315,852, - / Month). The added value of brahman cattle fattening business in Kabupaten OKU Timur is Rp. 59.305.278, - / tail (Rp 118.610.555, - / PP or Rp 19.768.426, - / Month). Brahman cattle fattening business in East OKU district can be said to be profitable and feasible to do. This is because the brackish cattle fattening business obtained NPV value at the bank interest rate of 18% (Rp 85.691.855, -) with the value of Net B / C of 1.89 and the value of IRR 32.16% which means feasible or effort can be done Because advantageous. So, brahman cattle fattening in Regency OKU East have good prospect to be developed.